Expression Patterns of PACAP and PAC1R Genes and Anorexigenic Action of PACAP1 and PACAP2 in Zebrafish - Nakamachi, Tomoya; Tanigawa, Ayano; Konno, Norifumi; Shioda, Seiji; Matsuda, Kouhei (Frontiers in Endocrinology, 2019)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide with potent suppressive effects on feeding behavior in rodents, chicken, and goldfish. Teleost fish express two PACAPs (PACAP1, encoded by the adcyap1a gene, and PACAP2, encoded by the adcyap1b gene) and two PACAP receptors (PAC1Rs; PAC1Ra, encoded by the adcyap1r1a gene, and PAC1Rb, encoded by the adcyap1r1b gene). However, the mRNA expression patterns of the two PACAPs and PAC1Rs, and the influence and relationship of the two PACAPs on feeding behavior in teleost fish remains unclear. Therefore, we first examined mRNA expression patterns of PACAP and PAC1R in tissue and brain. All PACAP and PAC1Rs mRNAs were dominantly expressed in the zebrafish brain. However, adcyap1a mRNA was also detected in the gut and testis. In the brain, adcyap1b and adcyap1r1a mRNA levels were greater than that of adcyap1a and adcyap1r1b, respectively. Moreover, adcyap1b and adcyap1r1a mRNA were dominantly expressed in telencephalon and diencephalon. The highest adcyap1a mRNA levels were detected in the brain stem and diencephalon, while the highest levels of adcyap1r1b were detected in the cerebellum. To clarify the relationship between PACAP and feeding behavior in the zebrafish, the effects of zebrafish (zf) PACAP1 or zfPACAP2 intracerebroventricular (ICV) injection were examined on food intake, and changes in PACAP mRNA levels were assessed against feeding status. Food intake was significantly decreased by ICV injection of zfPACAP1 (2 pmol/g body weight), zfPACAP2 (2 or 20 pmol/g body weight), or mammalian PACAP (2 or 20 pmol/g). Meanwhile, the PACAP injection group did not change locomotor activity. Real-time PCR showed adcyap1 mRNA levels were significantly increased at 2 and 3 h after feeding compared with the pre-feeding level, but adcyap1b, adcyap1r1a, and adcyap1r1b mRNA levels did not change after feeding. These results suggest that the expression levels and distribution of duplicated PACAP and PAC1R genes are different in zebrafish, but the anorexigenic effects of PACAP are similar to those seen in other vertebrates.